(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Patan Hospital (PH), Patan Academy of Health Sciences (PAHS) has separated non COVID and COVID emergencies for the safety of health care workers (HCWs). This study was conducted to assess the safety perception of healthcare workers working in emergency departments during the outbreak of COVID-19. Method: A cross sectional descriptive study was conducted among HCWs in non COVID and COVID emergency departments at PH, PAHS, Nepal, in April 2020 during COVID-19 outbreak. Questionnaires containing open and closed questions were used. Ethical approval was obtained. Result: Out of 72 HCWs, 58 (80.5%) responded, 47 (81%) felt need to have separate non COVID and COVID emergencies, 27 (46.6%) answered they were not comfortable working with the partial PPE (masks, gloves), 29 (50%) felt the need of having primary and secondary triaging. Conclusion: Emergency staff expressed need of having separate non COVID and COVID emergencies, and importance of primary and secondary triage.